Secondary Structures as Self-Organization Processes and Finishing Treatment of Friction Surfaces of Slide Bearings and Shafts. (2019) - Mironov, Alexander; Podrabinnik, Pavel; Kuznetsova, Ekaterina
Abstract: The article is devoted to the problem of replacing bronzes with cheaper aluminum alloys for slide bearings. The processes taking place on friction surface of both the aluminum alloy and steel counterbody are observed. The changes occurring during friction were investigated by scanning electron microscopy and energy-dispersive analysis. It has been revealed that secondary structures are formed on the surface during friction process and include all the chemical elements of the tribosystem which is a consequence of its self-organization. These structures are thin metal-polymer films containing mainly carbon and oxygen. Variety and content of alloying components is important as it defines the freedom degrees for self-organization.